PKM Pengelolaan Hasil Panen Jagung Pada Kelompok Tani Assamaturu Di Desa Paddinging Kecamatan Sanrobone Kabupaten Takalar - Bakhri, Syamsul; Mustafiah, Mustafiah; Darnengsih, D (PT.Mantaya Idea Batara, 2023)
Paddinging Village is located in Sanrobone District, Takalar Regency. The economy of the people in this village is generally based on agriculture, especially growing corn. Corn is a commodity needed by society and has good business value. This PKM activity was carried out in Paddinging Village, Sanrobone District, Takalar Regency, and the target audience was the Assamaturu Farmer Group. The main problem faced is that the target audience does not have an understanding of science and technology regarding the management of corn yields so that they have a high selling value. So far, the Target Audience uses a pick-sell pattern, that is, after the harvest is immediately sold, sadly it only sells to one buyer. The purpose of this PKM activity is for the Target Audience to have an understanding of science and technology in managing their corn yields so that they have a high selling value. The implementation of this PKM activity uses the Counseling Method, in which the Team provides directions on how to manage corn yields into corn products in the form of granules that are ready to be sold and of course have a high selling value. The results obtained from this PKM activity are that the Target Audience has an understanding of science and technology on how to manage their corn yields and is able to utilize 20% of the harvest to be processed into corn products in the form of granules ready for sale. In the future, it is hoped that more of the harvest will be processed into corn products in the form of granules so that it is expected to improve the farmers' economy.